Industry perceptions and community perspectives on advancing a hydrogen economy in Australia. (15th March 2023) - Beasy, Kim; Lodewyckx, Stefan; Mattila, Pauliina
Abstract: Investment in the hydrogen economy is increasing at unprecedented rates. To ensure a swift transition, understanding the diverse perspectives of and how to work collaboratively with all sectors of society is needed. In doing so, how industry stakeholders understand community perceptions and view their role in mediating perceived issues needs to be better understood. Therefore, this study aims to investigate how industry assumptions of community perspectives of hydrogen technologies compare and contrast with those in an Australian context. Using inductive thematic analysis, this exploratory project analysed 45 publicly-available submissions received in 2019 for the National Hydrogen Strategy from the industry perspective, and 62 public submissions received in 2019–2020 for the Victorian Green Hydrogen Discussion Paper from the community perspective. Results show that industry stakeholder assumptions about community concerns tended to reflect specific technical issues as opposed to those reported by the community: moral obligations to climate, environment, and future generations. Findings indicate that further work is needed to better align industry understandings and characterisations of the broader public. Several practical implications for the energy sector are noted. First, hydrogen is unlikely to be immune to community concerns faced by other energy projects; therefore, a robust plan for community inclusion that considers a range of complex, contextual factors is required. Second, there is an opportunity for the formation of a more collaborative approach, which integrates industry and community goals and values. Third, industry and government may benefit from viewing the community as an under-utilised, valuable partnership or resource rather than an object to be managed as part of a development process. We contend that a collaborative framework, including approaches such as co-design and shared identity formation may be critical to furthering the hydrogen agenda. Highlights: This study explores community and industry perspectives to advance hydrogen economy. Worldviews and values informed perspectives of industry and community stakeholders. Community perspectives were driven by future and greenhouse gas emission concerns. Industry assumed community would be most concerned about the safety of hydrogen. Results indicate that community and industry should be involved in unison.